IMPLEMENTASI MONITORING NILAI AKADEMIK DAN PRESENSI SISWA BERBASIS WEB PADA SMP IDN : THE IMPLEMENTATION OF WEB-BASED MONITORING OF ACADEMIC GRADES AND STUDENT ATTENDANCE AT IDN JUNIOR HIGH SCHOOLS - Mesra Betty Yel; Yuma Akbar; Frencis Matheos Sarimol; Abdulloh; Ari Ramadhan; Fadhil Khanifan Achmad; Untung Wahyudi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Academic value and student presence play an important role for every process of teaching and learning activities, especially to find out the level of learning success during school. However, these activities have not been carried out optimally because parents still experience difficulties in monitoring their child's learning activities in school and storing their data is still using paper stored in school documents so that data loss is easy. In analyzing, researchers use the SWOT (Strength, Weakness, Opportunity, Threat) method to analyze strengths, weaknesses, opportunities and threats. Researchers can conclude that with the application of monitoring academic values and attendance students are expected to be able to overcome these problems, this system is not just a data input media student presence and academic value but can also be used as a medium of attendance information and student academic value for parents so that he can monitor his son's daughter while in school. With the application of academic values and attendance students can reduce data loss and foster a sense of parental trust in school.